Projeto Cooperar: levantamento histórico da política de combate à pobreza rural no Estado da Paraíba em parceria com o Banco Mundial - SOUZA, Givaldo Alves Silva de (2015)
This work intends to present a brief report about the anti-poverty policies in Paraiba implemented in partnership with the World Bank for over 35 years. During this time the technical unit of state government running the program received several names like: Comissão Estadual de Planejamento Agrícola-CEPA, Projeto Nordeste-PB and finally Projeto Cooperar. At the beginning will be presented the historical issues that justify the policies to combat rural poverty implemented by the state government, as well as the Geographic, social and cultural characteristics. Conducted a rescue of institutionally history of this public policy in Paraiba. Presenting its evolution, characteristics and results since its foundation until the present day.